If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2c + 30 = 24 Reorder the terms: 30 + -2c = 24 Solving 30 + -2c = 24 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -2c = 24 + -30 Combine like terms: 30 + -30 = 0 0 + -2c = 24 + -30 -2c = 24 + -30 Combine like terms: 24 + -30 = -6 -2c = -6 Divide each side by '-2'. c = 3 Simplifying c = 3
| -4+20-6(-18)+(-11)= | | 14z-13z=5 | | -10m+2=-8m-8 | | 13d-12d=1 | | -6x+y = -3 | | x/7-1=-6 | | 230/30=345/x | | M/5=175.3 | | -5/6x-1/9x=-102 | | 6y+5y+4= | | 2/3(-2)-4 | | y=-5=1/3x | | 5s-3s=14 | | 12 = g3+ 9 | | 5/13.75=p/24.75 | | 5.04/-9 | | 21.6-1a=5d | | f(x)=7x^2+2x | | -3b=b-8 | | 5/$13.75=p/$24.75 | | x+4y+2z=-11 | | 2b+4b=18 | | 4x-y-z=1 | | Kt(-9)=7 | | 22-2(2a+1)=6w-2(6+w) | | x+y+5z=-8 | | 3.1n-0.03=-9 | | 6(x+24)(x-6)+3(x+12)(x-18)=19(x+45)-(x-36) | | 5w^7/w6 | | 15=18+t | | 6(x+24)(x-6)+3(x+12)(x-18)=18(x+45)-(x-36) | | Y=-21+3 |